Blood viscosity in patients with diffuse large B cell non-Hodgkin’s lymphoma - Utkan, G.; Tek, I.; Kocer, M.; Muallaoglu, S.; Durnalı, A.G.; Arslan, U.Y.; Celenkoglu, G.; Tokluoglu, S.; Alkis, N. (Experimental Oncology, 2006)
The aim of the study was to evaluate blood viscosity as possible marker of disease progression in patients with newly diagnosed non-Hodgkin’s lymphoma (NHL). Methods: The viscosity of blood samples from 20 patients with newly diagnosed aggressive NHL (stage I, n = 7; stage II, n = 4; stage III, n = 7; stage IV, n = 2) was analyzed using Brookfield DV-II + (USA) machine. Results: Blood viscosity in NHL patients (median: 5.5 ± 1.46 miliPascal) inversely correlated with lactatdehydrogenase (LDH) level, international prognostic index (IPI) score, and stage (p = 0.02, r= –0.51; p = 0.03, r= –0.63; and p = 0.04, r= –0.45, respectively) and positively correlated with hemoglobin level (p = 0.02, r = 0.65)). Conclusion: According to our data, blood viscosity may be considered as a follow up marker in NHL patients along with LDH level or sedimentation rate.